Synchrotron X-Ray Radiation-Induced Bystander Effect: An Impact of the Scattered Radiation, Distance From the Irradiated Site and p53 Cell Status - Lobachevsky, Pavel; Forrester, Helen B.; Ivashkevich, Alesia; Mason, Joel; Stevenson, Andrew W.; Hall, Chris J.; Sprung, Carl N.; Djonov, Valentin G.; Martin, Olga A. (Frontiers in Oncology, 2021)
Synchrotron radiation, especially microbeam radiotherapy (MRT), has a great potential to improve cancer radiotherapy, but non-targeted effects of synchrotron radiation have not yet been sufficiently explored. We have previously demonstrated that scattered synchrotron radiation induces measurable γ-H2AX foci, a biomarker of DNA double-strand breaks, at biologically relevant distances from the irradiated field that could contribute to the apparent accumulation of bystander DNA damage detected in cells and tissues outside of the irradiated area. Here, we quantified an impact of scattered radiation to DNA damage response in “naïve” cells sharing the medium with the cells that were exposed to synchrotron radiation. To understand the effect of genetic alterations in naïve cells, we utilised p53-null and p53-wild-type human colon cancer cells HCT116. The cells were grown in two-well chamber slides, with only one of nine zones (of equal area) of one well irradiated with broad beam or MRT. γ-H2AX foci per cell values induced by scattered radiation in selected zones of the unirradiated well were compared to the commensurate values from selected zones in the irradiated well, with matching distances from the irradiated zone. Scattered radiation highly impacted the DNA damage response in both wells and a pronounced distance-independent bystander DNA damage was generated by broad-beam irradiations, while MRT-generated bystander response was negligible. For p53-null cells, a trend for a reduced response to scattered irradiation was observed, but not to bystander signalling. These results will be taken into account for the assessment of genotoxic effects in surrounding non-targeted tissues in preclinical experiments designed to optimise conditions for clinical MRT and for cancer treatment in patients.